AI and Automated Systems for Information Technology Operations - Latha Narayanan Valli (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Over the last several years, the research community devoted to information technology (IT) has paid more attention to artificial intelligence. However, there is a growing fear that AI research would not experience the same kind of cumulative buildup of knowledge as IT research has in the past. This study addresses this topic, which conducts a thorough literature analysis of artificial intelligence research in IT between the years 2008 and 2022. As a result of this, the study makes a number of significant contributions, including (i) a tabulation of the benefits of AI to IT enterprises, (ii) consequences for future study and actual use of AI, and (iii) potential avenues for further study in the field of artificial intelligence.